T follicular helper cell is essential for M2 macrophage polarization and pulmonary vascular remodeling in hypoxia-induced pulmonary hypertension - Cheng Li; Pingping Liu; Hao Zhu; Huan Yang; Jun Zha; Huiling Yao; Shaoze Zhang; Jin Huang; Guang Li; Gang Jiang; Yongliang Jiang; Aiguo Dai (Respiratory Research)
Abstract Background Hypoxia-induced pulmonary hypertension (HPH) is a subgroup of type 3 pulmonary hypertension that may cause early right ventricular failure and eventual cardiac failure, which lacks potential therapeutic targets. Our previous research demonstrated that T follicular helper (TFH) cells that produce IL-21 were involved in HPH. However, the molecular mechanisms of TFH/IL-21-mediated pathogenesis of HPH have been elusive. Here we investigate the role of TFH cells and IL-21 in HPH. Methods Studies were performed in C57BL/6 mice or IL-21 knockout mice exposed to chronic hypoxia to induce PH, and examined by hemodynamics. Molecular and cellular studies were performed in mouse lung and pulmonary arterial smooth muscle cells (PASMCs). M2 signature gene (Fizz1), M1 signature genes (iNos, IL-12β and MMP9), GC B cell and its marker GL-7, caspase-1, M2 macrophages, TFH cells, Bcl-6 and IL-21 level were measured. Proliferation rate of PASMCs was measured by EdU. Pyroptosis was assessed using Hoechst 33,342/PI double fluorescent staining. Results In response to chronic hypoxia exposure-induced pulmonary hypertension, IL-21−/− mice or downregulation of TFH cells in WT mice developed blunted pulmonary hypertension, attenuated pulmonary vascular remodelling. Furthermore, chronic hypoxia exposure significantly increased the germinal center (GC) B cell responses, which were not present in IL-21−/− mice or downregulation of TFH cells in WT mice. Importantly, IL-21 promoted the polarization of primary alveolar macrophages toward the M2 phenotype. Consistently, significantly enhanced expression of M2 macrophage marker Fizz1 were detected in the bronchoalveolar lavage fluid of HPH mice. Moreover, alveolar macrophages that had been cultivated with IL-21 promoted PASMCs proliferation and pyroptosis in vitro, while a selective CX3CR1 antagonist, AZD8797 (AZD), significantly attenuated the proliferation and pyroptosis of the PASMCs. Finally, ECM1 knockdown promoted IL-2–STAT5 signaling and inhibited Bcl-6 signaling to inhibit TFH differentiation in HPH. Conclusions TFH/IL-21 axis amplified pulmonary vascular remodelling in HPH. This involved M2 macrophage polarization, PASMCs proliferation and pyroptosis. These data suggested that TFH/IL-21 axis may be a novel therapeutic target for the treatment of HPH.